How do the general population behave with facemasks to prevent COVID-19 in the community? A multi-site observational study - Colin Deschanvres (Antimicrobial Resistance and Infection Control, 2021)
Abstract Objective The appropriate use of facemasks, recommended or mandated by authorities, is critical to prevent the spread of COVID-19 in the community. We aim to evaluate frequency and quality of facemask use in general populations. Methods A multi-site observational study was carried out from June to July 2020 in the west of France. An observer was positioned at a predetermined place, facing a landmark, and all individual passing between the observer and the landmark were included. The observer collected information on facemask use (type, quality of positioning), location and demographic characteristics. Results A total of 3354 observations were recorded. A facemask was worn by 56.4% (n = 1892) of individuals, including surgical facemasks (56.8%, n = 1075) and cloth masks (43.2%, n = 817). The facemask was correctly positioned in 75.2% (n = 1422) of cases. The factors independently associated with wearing a facemask were being indoors (adjusted odds ratio [aOR], 2.7; 95% confidence interval [CI] 2.28–3.19), being in a mandatory area (aOR, 6.92; 95% CI 5–9.7), female gender (aOR, 1.75; 95% CI 1.54–2.04), age 41–65 years (aOR, 1.7; 95% CI 1.43–2.02) and age > 65 years (aOR, 2.28; 95% CI 1.83–2.85). The factors independently associated with correct mask position were rural location (aOR, 1.38; 95% CI 1.07–1.79), being in an indoor area (aOR, 1.85; 95% CI 1.49–2.3), use of clothmask (aOR, 1.53; 95% CI 1.23–1.91), and age > 40 years (aOR, 1.75 95%CI 1.37–2.23). Conclusions During the initial phase of the COVID-19 pandemic, the frequency and quality of facemask wearing remained low in the community setting. Young people in general, and men in particular, represent the priority targets for information campaigns. Simplifying the rules to require universal mandatory facemasking seemed to be the best approach for health authorities.